Upaya Meningkatkan Hasil Belajar Matematika Siswa Pada Materi Pembagian Di Kelas IV Di UPT SDN 06 Bagan Dalam Menggunakan Model Ekspositori - Irma Yulisa; Fauzi Fadliansyah (KRAKATAU (Indonesian of Multidisciplinary Journals), 2024)
Mathematics subjects need to be given to all students starting from elementary Mathematics subjects need to be given to all students starting from elementary school with the aim of equipping students with the ability to think logically, analytically, systematically, critically, creatively and collaboratively. These skills are necessary to enable students to acquire, manage, and use information. Mathematics is defined in the Big Indonesian Dictionary (KBBI) as the science of numbers, relationships between numbers, and operational procedures for solving problems related to numbers (Hasan Alwi, 20012: 723). Aristotle (quoted in Moeharti Hadiwijaya, 1996: 20) said that mathematics is one of the three foundations that divide science into natural science, mathematics and theology. The expository learning model is a learning model that focuses on the process where "a teacher orally (orally and in writing) conveys material or materials to a group of students with the aim of maximizing students' mastery of the material".